Middle corridor - policy development and trade potential of the Trans-Caspian International Transport Route - Tristan Kenderdine; Péter Bucsky (Asian Development Bank Institute (ADBI), 2021)
The Trans-Caspian International Transport Route (TITR), known as the Middle Corridor, is a multilateral institutional development linking the containerized rail freight transport networks of the People's Republic of China (PRC) and the European Union through the economies of Central Asia, the Caucasus, Turkey, and Eastern Europe. The multilateral, multimodal transport institution links Caspian and Black Sea ferry terminals with rail systems in the PRC, Kazakhstan, Azerbaijan, Georgia, Turkey, Ukraine, and Poland. Trans-Eurasian and intra-Eurasian rail freight development remains fundamentally policy- and subsidy-driven on the PRC side, yet dependent on European Union demand-side drivers to create traffic flow volumes. The development of the Middle Corridor, though, is institutionally independent and potentially transformative for the economies of Central Asia, the Caucasus, and Turkey. We explore the institutional development of transport infrastructure and economic potential from three macroregional angles: policy- and subsidy-driven development, the Central Asia - Caucasus - Turkey physical industrial geography and political institution limitations, and lack of demand-side fundamentals from European Union market agents. The PRC's supply-side-policy evidence suggests that growth in transcontinental containerized rail transport is politically feasible. However, demand-side factors suggest that trade development potential is largely limited to greater extraregional connectivity from the Middle Corridor economies with little economic rationale for increased PRC - Europe transcontinental freight flows.
Keywords: B15; B27; B52; E02; E61; F1; 330; transport policy; economic geography; geoindustrial policy; industrial policy; Eurasian economic integration